“What is in a name?”—Definition of mental disorder in the last 50 years: a scoping review, according to the perspective of clinical psychology - Petretto, Donatella Rita; Mura, Alessandro; Carrogu, Gian Pietro; Gaviano, Luca; Atzori, Riccardo; Vacca, Mattia (Frontiers in Psychology, 2025)
BackgroundSince ancient times, and later in the 17th and 18th centuries, scholars have sought to classify mental disorders. However, it wasn’t until the late 1970s, with the work of Spitzer and Endicott and the publication of the DSM-III, that a formal definition of mental disorder was established. Once this milestone was reached, a long and complex debate on the definition of mental disorder started. Here we aim to review such a debate, taking into consideration the papers that have proposed and/or investigated and discussed the various definitions of mental disorder over the past 50 years.MethodsWe conducted the literature review via Scopus, PubMed, and Web of Science databases. The following inclusion criteria were established: papers on the definition of mental disorder, written in English. All study designs were eligible, including those that utilized qualitative and quantitative methods, as well as methodology or guideline reports.ResultsThe sorted papers (n = 64) showed a complex, long and still ongoing debate on the definition of mental disorder. Only few authors directly proposed their own definitions, while others analyzed, discussed, criticized and/or proposed integrations to previous or current definitions. The authors of the selected papers conducted their work alongside the development of various editions of the main international diagnostic manuals (primarily the DSM). Many of them directly engaged with past and present definitions of mental disorder provided in the mentioned manuals or referenced different editions of both DSM and ICD.ConclusionWe concluded that despite the complex and still ongoing debate on the topic, and the precious contributions from all the authors involved, a unique and agreed-upon definition of the concept of mental disorder is still far from being identified. Furthermore, even if the definitions proposed by the international diagnostic manuals (especially by the DSM) constitutes an undeniable landmark, such definitions resulted to be more the outcome of various discussions, than the fruit of a shared consensus. The construct of mental disorder and its shared definition remain a critical theme in psychopathology.